2022
DOI: 10.9734/ijtdh/2022/v43i230578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-procedure Anxiety Levels on Post-procedure Pain Scores in Women Undergoing Hysterosalpingography in South-south Nigeria

Abstract: Background: Infertility is the inability of a couple to conceive after one year of regular, unprotected sexual intercourse. Hysterosalpingography plays a very crucial role the evaluation of the women with infertility. Objective: To determine the relationship between pre-procedure anxiety and procedure-associated pain among infertile women undergoing hysterosalpingography. Materials and Methods: This prospective survey was conducted at the Obstetrics and Gynaecology, and Radiology Departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This activation relays a neural signal through the hypothalamus to stimulate the release of preganglionic acetylcholine, which is a neurotransmitter. Acetylcholine, in turn stimulates the release of epinephrine and norepinephrine, which are catecholamine from the adrenal cortex [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activation relays a neural signal through the hypothalamus to stimulate the release of preganglionic acetylcholine, which is a neurotransmitter. Acetylcholine, in turn stimulates the release of epinephrine and norepinephrine, which are catecholamine from the adrenal cortex [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Kiridi KE [7] revealed that there was a significant, positive, and strong relationship between pre-procedure anxiety and post-procedure pain. This is in keeping with the report from the study of Tokmak et al [14] where there was significant positive correlation between the level of pre-procedure anxiety and the level of post-Hysterosalpingography pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and stress can enhance the procedure-associated pain of hysterosalpingography. 8 Two pain score scales were used in this research. The VAS was used to score the level of pain that the women expressed at different steps of this investigative modality, while the numerical rating scale (NRS) was used to score the overall pain perception at the end of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the major shortcomings of hysterosalpingography is discomfort and/or pain for the patient during or after the investigative modality; and this is a major cause of anxiety for many patients. 8 Patients feel pain at various points during hysterosalpingography. In our practice, individual patients may feel pain during the insertion of speculum, grasping the lip of the cervix with a tenaculum, insertion of the canula or injection of contrast media into the uterine cavity.…”
mentioning
confidence: 99%
“…It causes a lot of stress and anxiety for the couple involved. 1 About 17% of couples worldwide, are affected by infertility. It is defined as the inability to conceive after 12 months of adequate and regular unprotected, peno-vaginal, ejaculatory sexual intercourse.…”
Section: Introductionmentioning
confidence: 99%